Early Detection of Learning Problems: Questions, Cautions, and Guidelines. - Keogh, Barbara K.; Becker, Laurence D. (Exceptional Children, 1973)
Assumptions underlying programs of early identification of young children viewed as educationally ‘at risk’ are reviewed in terms of the research literature relevant to questions of validity of identifying or screening techniques, implications of recognition for remediation, and possible compounding negative effects of early identification. Guidelines for development and implementation of programs of early detection are proposed. Recommendations include emphasis upon techniques which are short term and educationally oriented and which are based on functional aspects of children's behavior in classroom settings.